Consumer Protection against Unauthorised Use of Credit Cards in Malaysia: A Banking Law Perspective - Maruthavanar, Kalavathy (Journal of Malaysian and Comparative Law, 2008)
This article examines protection afforded to consumers in the credit card industry with reference to guidelines issued by Bank Negara that govern 'unauthortised use' of credit cards in Malaysia. The first consumer protection guideline that governs plastic cards as well as other forms electronic transactions (excluding internet banking) is BNM/GP 11. The article discusses the scope of protection offered by the aforesaid guideline to credit card holders. However it is an omnibus guideline as it covers all forms of electronic transactions and not designed specifically for credit card usage. Another guideline analysed is the more recent guideline known as Credit Card Guidelines (BNM/RII/GLO14-1), which is specifically designed for credit card usage in Malaysia. The credit card industry uses the Credit Card Guidelines (BNM/GLO14-1) as the standard to be implemented for credit card usage in Malaysia. The only set back in its implementation, has been the controversy as to whether such a guideline as the force of law.